1997
DOI: 10.1080/07448481.1997.9936889
|View full text |Cite
|
Sign up to set email alerts
|

Restricting Smoking at the University of Köln, Germany: A Case Study

Abstract: The effects of a new policy limiting smoking to separate, designated areas in School of Education buildings at the University of Köln, Germany, were analyzed. Although the majority (77%) of the 1,223 students surveyed did not expect the changed policy to affect their smoking habits, approximately 28% of the men and 30% of the women said they were smoking less at the university after the change went into effect. Ninety-one percent of the nonsmoking students and 68% of the smokers supported the new policy. Smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…210,444–449 A limited number of quasi-experimental evaluations with only short-term (1 to 4 months) follow-up demonstrated mixed findings, with no consistent evidence for the effects of campus smoking restrictions on active smoking or cessation. 450,451 …”
Section: Resultsmentioning
confidence: 99%
“…210,444–449 A limited number of quasi-experimental evaluations with only short-term (1 to 4 months) follow-up demonstrated mixed findings, with no consistent evidence for the effects of campus smoking restrictions on active smoking or cessation. 450,451 …”
Section: Resultsmentioning
confidence: 99%
“…3,6,13,15,16,22 Yet, few strategies to improve compliance have been evaluated prior to this Ambassador Program. 15,27 We found that the TFTA!…”
Section: Resultsmentioning
confidence: 99%
“…Both policy violator observation and cigarette butt data have been used to collect objective compliance data. 15,16,19,21-23,27 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sim et al has reported that 69.2% of smokers would never smoke at public places under no-smoking sign boards [19]. Apel et al reported that the designation of smoking-free areas in campus buildings resulted in a decrease in the number of cigarettes smoked [20]. Borders et al found that clear identification or designation of non-smoking areas on campus significantly decreased the odds of smoking by 45% [21].…”
Section: Discussionmentioning
confidence: 99%